TOBACCO STRATEGY (Tufts Archival Research Center, 2007)
Analysis of tobacco strategy and position of numerous conservative organizations. Focuses mainly on the federal excise tax issue and the proposed Health Security Act. Indicates high level of cooperation between Philip Morris and conservative interest groups.